Withdrawing ixekizumab in patients with psoriatic arthritis who achieved minimal disease activity: results from a randomized, double-blind withdrawal study - Coates, LC; Pillai, SG; Tahir, H; Valter, I; Chandran, V; Kameda, H; Okada, M; Kerr, L; Alves, D; Park, SY; Adams, DH; Gallo, G; et al. (Wiley, 2021)
Objective To evaluate the effect of withdrawing ixekizumab in patients with psoriatic arthritis (PsA) in whom minimal disease activity (MDA) has been achieved after open-label ixekizumab treatment.